1993
DOI: 10.1136/bmj.307.6902.489
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia sans frontieres: concepts of schizophrenia among French and British psychiatrists.

Abstract: Objective-To compare the first admission rates for schizophrenia in Conclusions-British and French psychiatrists use different diagnostic criteria and contrasting methods oftreatment for schizophrenia. Differences in diagnostic criteria probably contribute towards the disparity in administrative incidence rates and time trends for schizophrenia in the two countries. Doctors in the European Community can now work in any country. Further work is needed to ensure psychiatrists are talking a common language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 7 publications
0
23
0
1
Order By: Relevance
“…The 158 included studies were drawn from 32 countries. One study [13] provided rates for seven countries, and another provided rates for two countries [74]. Details of these studies are shown in Table S1 in Additional File 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 158 included studies were drawn from 32 countries. One study [13] provided rates for seven countries, and another provided rates for two countries [74]. Details of these studies are shown in Table S1 in Additional File 4.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 13 included at least one rate with person years as the denominator [9,21,31,42,74,93,121,130,133,152,163,167,174]. Person-year incidence rates have been used in descriptive and model-based analyses alongside crude annual rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different concepts about diagnosis and treatment among psychiatrists in different countries are well known [19]. Schizophrenia was chosen as a study diagnosis, because it is generally regarded as having similar incidence between different cultures and times [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an ambitious international investigation, the US/UK Diagnostic Project (Cooper et al 1972), revealed that American psychiatrists made the schizophrenia diagnosis twice as much as their colleagues from Britain, even though both teams made use of identical diagnostic criteria. And as late as 1993, it turned out that French and English psychiatrists were still using substantially different concepts of schizophrenia (Van Os et al 1993).…”
Section: Is Schizophrenia Objectively Real?mentioning
confidence: 99%